Implementation Of Lean Management Methods In Improving Operational Efficiency And Reducing Waste In Manufacturing Companies - Nasution, Nahdiyah; Harahap, Adinda Putri (Marcha Institute, 2023)
This research investigates the application of Lean Management methods in the context of a manufacturing company with the aim of improving operational efficiency and reducing waste. Through value stream analysis, elimination of wastage, implementation of Just-in-Time systems, utilisation of technology and automation, employee training, and establishment of a Lean culture, this research demonstrates that holistic implementation of Lean can yield significant results in improving productivity and product quality while reducing production costs. The research also identifies certain limitations in the context of Lean Management implementation and offers suggestions for future research development, including a focus on deeper influence factors and the integration of Industry 4.0 concepts with Lean Management.